The use of technology in the classroom and its incidence on english learners' proficiency at the Foreign Language Department, University of El Salvador - Méndez Rodríguez, Sergio Otoniel; Ardón Mojica, William Alfredo; Llanes Márquez López, Jorge Homero; Garay Salinas, Ricardo (San Salvador, El Salvador : Universidad de El Salvador, 2011)
The research had as a main goal to demonstrate that the use of technological resources in the classroom may influence in student’s daily life when learning English as a second or foreign language and make them more efficient by the time when they have to put them into practice in their real job. For that reason the researchers make a specific emphasis about the great advantages that many teachers and professors have nowadays when they make a good usage of different technological resources when teaching a class. The purpose of the present research is to describe the importance that the use of technology has in the classroom. Taking into account that the new generations demand, and at the same time require, the use of many technological resources to develop any specific activity, this research has been focused on how essential it is the use of this for many teachers, not only because it makes their life easier but also because by doing that they get better results at the end of a particular class.
Anexos
Thesis in order to obtain the degree of -- (Licenciatura en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2011
Bibliografía : hoja 55
Audiencia general.
La tesis también está en formato digital.
Keywords: Inglés -- Enseñanza; Materiales de enseñanza; Tecnología educativa